The Effects of Characteristics of the Board of Commissioners and Audit Committee on the Level of Risk Disclosure in Financial Sector Service Companies in the Banking Sector Listed on the Indonesia Stock Exchange in the Period 2015-2017 - Hasibuan, David H M; Auliya, Meiliani (Kesatuan Press, 2019)
The aim of this study is to examine the effects of the board of commissioners and audit committee characteristics such as the proportion of independent commissioners, the board of commissioner size, frequency of board meetings, audit committee size, the proportion of independent audit committee and frequency of audit committee meetings on the level of risk disclosures. The results show that the frequency of board meetings, the proportion of independent audit committee and frequency of audit committee meetings significantly affect the level of risk disclosures, while the proportion of independent commissioners, the board of commissioner size, and audit committee size do not significantly affect the level of risk disclosures. The results show that the proportion of independent commissioners, the board of commissioner size, frequency of board meetings, audit committee size, the proportion of independent audit committee and frequency of audit committee meetings simultaneously have significant effects on the level of risk disclosures. The results of the study provide investors the information regarding the risk that companies could have, and they are also useful as a basis for making decisions